Зовнішні умови функціонування інституту банкрутства в економіці України - Ilkova, Nika; Rynkevych, Natalia (Dr. Viktor Koval, 2018)
Introduction. In modern conditions of Ukrainian economy development, it is interesting to justify certain measures to support enterprises in the conditions of national economy dependence on fluctuations in the world market and the inflation growth, in order to ensure the stability of business entity functioning in all spheres of the economy. Under such circumstances, effective bankruptcy institute functioning becomes of particular importance, since the possibility of industrial production growth, employment level increase and people life quality improvement depends on the financial recovery of enterprises of real sector economy. Aim and tasks. The aim of the article is to study external conditions of bankruptcy Institute functioning in the economy of Ukraine and their modern transformation. The obtained results determine what exactly should be done in the direction of further improvement of the regulatory instruments of state policy in this area. To achieve the goal, it has been used a complex of scientific research complementary methods of economic processes and phenomena, with an application of statistical and analytical materials, as well as the results of authors scientific research. Results. As a result of a study of external conditions of bankruptcy Institute functioning in the economy of Ukraine, it is determined that existing macroeconomic environment has a significant impact on its character of functioning, defining the goals and objectives of further transformation processes regulation. It is determined that the external factors of the macroeconomic environment are the most threatening because there is almost no opportunity to influence them at the enterprise level. In the research, the peculiarities of the external conditions of bankruptcy Institute functioning in the economy of Ukraine are identified based on the use of indicators that directly or indirectly help determine the effectiveness of bankruptcy institute, the laws of its development, and interaction of social, political, economic and other processes at the macro level. Conclusions. On the basis of the obtained results, it can be determined that most indicators testify difficult external conditions of bankruptcy institute functioning, with a certain improvement of the situation in recent years. Thereby, there is a need for further bankruptcy institute transformation, in order to maintain the balance between the interests of the state, economic entities, competitive market environment, and entrepreneurial activity risk minimization.